Evaluasi Aspek Usabilitas pada Sistem Informasi Manajemen Puskesmas Menggunakan Pendekatan Heuristik - Fahmitra, Novrizal; Kusuma, Hollanda (Pusat riset dan Inovasi Nasional, 2025)
This study aims to conduct an analysis of the management information system implemented at the community health center (Puskesmas). In fulfilling its operational functions, Puskesmas typically utilizes a management information system to support data processing and the delivery of healthcare services. To enable healthcare personnel to perform their duties more effectively and efficiently, the system must operate in an optimal condition. Ensuring such efficiency requires a systematic evaluation to identify existing issues, thereby allowing for targeted improvements and further system development. The evaluation was carried out using a heuristic evaluation approach focused on usability aspects, referencing ten standard indicators. Data were collected through the distribution of questionnaires to clinical staff at Puskesmas. The results of the analysis identified 15 usability-related issues distributed across 4 key usability aspects. These issues were subsequently categorized into low and medium priority levels for improvement. The findings from this study may serve as a foundation for system refinement, feature enhancement, and overall development of the management information system at Puskesmas Depok I, Sleman, ultimately aiming to improve user experience in terms of accessibility and operational convenience.